Horseweed (Conyza canadensis) Suppression from Cover Crop Mixtures and Fall-Applied Residual Herbicides. (8th March 2019) - Pittman, Kara B.; Barney, Jacob N.; Flessner, Michael L.
Abstract: Horseweed is a problematic weed to control, especially in no-tillage production. Increasing cases of herbicide resistance have exacerbated the problem, necessitating alternative control options and an integrated weed management approach. Field experiments were conducted to evaluate horseweed suppression from fall-planted cover crop monocultures and mixtures as well as two fall-applied residual herbicide treatments. Prior to cover crop termination, horseweed density was reduced by 88% to 96% from cover crops. At cover crop termination in late spring, cereal rye biomass was 7, 671 kg ha –1, which was similar to cereal rye–containing mixtures (7, 720 kg ha –1 ) but greater than legumes in monoculture (3, 335 kg ha –1 ). After cover crops were terminated in late spring using a roller crimper, corn and soybeans were planted and horseweed was evaluated using density counts, visible ratings, and biomass collection until harvest. Forage radish winterkilled, offering no competition in late winter or biomass to contribute to horseweed suppression after termination. Excluding forage radish in monoculture, no difference in horseweed suppression was detected between cereal rye–containing cover crops and legumes (crimson clover and hairy vetch) in monoculture. Likewise, horseweed suppression was similar between monocultures and mixtures, with the exception of one site-year in which mixtures provided better suppression. In this experiment, the cover crop treatments performed as well as or better than the fall-applied residual herbicides, flumioxazin+paraquat and metribuzin+chlorimuron-ethyl. These results indicate that fall-planted cover crops are a viable option to suppress horseweed and can be an effective part of an integrated weed management program. Furthermore, cover crop mixtures can be used to gain the benefits of legume or brassica cover crop species without sacrificing horseweed suppression.